Ground-state phase diagram, fermionic entanglement and kinetically-induced frustration in a hybrid ladder with localized spins and mobile electrons. (7th August 2017) - Carvalho, R C P; Pereira, M S S; de Oliveira, I N; Strečka, J; Lyra, M L
Abstract: We introduce an exactly solvable hybrid spin-ladder model containing localized nodal Ising spins and interstitial mobile electrons, which are allowed to perform a quantum-mechanical hopping between the ladder's legs. The quantum-mechanical hopping process induces an antiferromagnetic coupling between the ladder's legs that competes with a direct exchange coupling of the nodal spins. The model is exactly mapped onto the Ising spin ladder with temperature-dependent two- and four-spin interactions, which is subsequently solved using the transfer-matrix technique. We report the ground-state phase diagram and compute the fermionic concurrence to characterize the quantum entanglement between the pair of interstitial mobile electrons. We further provide a detailed analysis of the local spin ordering including the pair and four-spin correlation functions around an elementary plaquette, as well as, the local ordering diagrams. It is shown that a complex sequence of distinct local orderings and frustrated correlations takes place when the model parameters drive the investigated system close to a zero-temperature triple coexistence point.